KONDISI PEMBELAJARAN SENI BUDAYA (MUSIK) DI KELAS VII SMP NEGERI 3 LUNANG KABUPATEN PESISIR SELATAN - Raflesi, Mike Febry; Sudarman, Yos; Lumbantoruan, Jagar (SENDRATASIK UNP, 2019)
AbstractThis study aims to determine the learning conditions of Cultural Arts (Music) in Class VII of SMP Negeri 3 Lunang, South Coastal District, where the background of the problem is the implementation of the 2006 KTSP curriculum, and the problem of lack of learning activities and learning facilities. This type of research is qualitative research with a descriptive analysis approach. The object of this study is a cultural arts teacher who teaches in class VII of Lunang 3 Public Middle School, Pesisir Selatan District. Data is collected through observation, interviews, documentation, and literature. The results of the study indicate that the convergence of art and culture learning in SMP Negeri 3 Lunang, Pesisir Selatan District, which still applies KTSP, has raised various problems regarding the conditions of learning in the arts and culture. Teachers who often do not carry out learning, inappropriate music art subject matter, and inadequate learning facilities have caused the conditions of learning arts and culture in this school to experience shortcomings and in accordance with the expected targets.Keywords: Learning, Curriculum, Cultural Arts (Music)